Public debt management, monetary policy and financial institutions - Márcio G. P. Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2002)
Despite the large size of the Brazilian debt market, as well the large diversity of its bonds, the picture that emerges is of a market that has not yet completed its transition from the role it performed during the megainflation years, namely that of providing a liquid asset that provided positive real returns. This unfinished transition is currently placing the market under severe stress, as fears of a possible default from the next administration grow larger. This paper analyzes several aspects pertaining to the management of the domestic public debt. The causes for the extremely large and fast growth of the domestic public debt during the seven-year period that President Cardoso are discussed in Section 2. The main culprit is the very high and risky interest rate, with the recognition of old debts (hidden liabilities and state debt renegotiation) coming in second. Section 3 computes Value at Risk and Cash Flow at Risk measures for the domestic public debt. These risk measures show that the current composition of the public debt is very risky. The rollover risk is introduced in a mean-variance framework in Section 4, and the maturity structure evolution is discussed. The increased riskness was the cost to improve the maturity structure. Section 5 discusses a few issues pertaining to the overlap between debt management and monetary policy. Finally, Section 6 wraps up with policy discussion and policy recommendations.
Keywords: 330; Öffentliche Schulden; Schuldenmanagement; Geldpolitik; Brasilien